Single deepest vertical pocket or amniotic fluid index as evaluation test for predicting adverse pregnancy outcome (SAFE trial): a multicenter, open‐label, randomized controlled trial. (June 2016) - Kehl, S.; Schelkle, A.; Thomas, A.; Puhl, A.; Meqdad, K.; Tuschy, B.; Berlit, S.; Weiss, C.; Bayer, C.; Heimrich, J.; Dammer, U.; Raabe, E.; et al.
ABSTRACT: Objective: To determine whether the amniotic fluid index (AFI) or the single deepest vertical pocket (SDP) technique for estimating amniotic fluid volume is superior for predicting adverse pregnancy outcome. Methods: This was a multicenter randomized controlled trial including 1052 pregnant women with a term singleton pregnancy across four hospitals in Germany. Women were assigned randomly, according to a computer‐generated allocation sequence, to AFI or SDP measurement for estimation of amniotic fluid volume. Oligohydramnios was defined as AFI ≤ 5 cm or the absence of a pocket measuring at least 2 × 1 cm. The diagnosis of oligohydramnios was followed by labor induction. The primary outcome measure was postpartum admission to a neonatal intensive care unit. Further outcome parameters were the rates of diagnosis of oligohydramnios and induction of labor (for oligohydramnios or without specific indication), and mode of delivery. Results: Postpartum admission to a neonatal intensive care unit was similar between groups (4.2% ( n = 21) vs 5.0% ( n = 25); relative risk (RR), 0.85 (95% CI, 0.48–1.50); P = 0.57). In the AFI group, there were more cases of oligohydramnios (9.8% ( n = 49) vs 2.2% ( n = 11); RR, 4.51 (95% CI, 2.2–8.57); P < 0.01) and more cases of labor induction for oligohydramnios (12.7% ( n = 33) vs 3.6% ( n = 10); RR, 3.50 (95% CI, 1.76–6.96); P < 0.01) than in the SDP group. Moreover, an abnormal cardiotocography was seen more often in the AFI group than in the SDP group (32.3% ( n = 161) vs 26.2% ( n = 132); RR, 1.23 (95% CI, 1.02–1.50); P = 0.03). The other outcome measures were not significantly different between the two groups. Conclusions: Use of the AFI method increased the rate of diagnosis of oligohydramnios and labor induction for oligohydramnios without improving perinatal outcome. The SDP method is therefore the favorable method to estimate amniotic fluid volume, especially in a population with many low‐risk pregnancies. Copyright © 2015 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article has been selected for Journal Club. Clickhere to view slides and discussion points. This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.